Genome-Scale Metabolic Model Driven Design of a Defined Medium for Campylobacter jejuni M1cam - Tejera, Noemi; Crossman, Lisa; Pearson, Bruce; Stoakes, Emily; Nasher, Fauzy; Djeghout, Bilal; Poolman, Mark; Wain, John; Singh, Dipali (Frontiers in Microbiology, 2020)
Campylobacter jejuni, the most frequent cause of food-borne bacterial gastroenteritis, is a fastidious organism when grown in the laboratory. Oxygen is required for growth, despite the presence of the metabolic mechanism for anaerobic respiration. Amino acid auxotrophies are variably reported and energy metabolism can be through several electron donor/ acceptor combinations. Overall, the picture is one of a flexible, but vulnerable metabolism. To understand Campylobacter metabolism, we have constructed a fully curated, metabolic model for the reference organism M1 (our variant is M1cam) and validated through laboratory experiments. Our results show that M1cam is auxotrophic for methionine, niacinamide and pantothenate. There are complete biosynthesis pathways for all amino acids except methionine and it can produce energy, but not biomass, in the absence of oxygen. M1cam will grow in DMEM/F-12 defined media but, not in the previously published Campylobacter specific defined media tested. Using the model, we identified potential auxotrophies and substrates that may improve growth. With this information, we have designed a simple defined media containing inorganic salts, the auxotrophic substrates, L-methionine, niacinamide and pantothenate, and pyruvate and additional amino acids L-cysteine, L-serine and L-glutamine for growth enhancement. Our defined media supports 1.75-fold higher growth rate than Brucella broth after 48 hours at 37 ◦ C and sustains growth of other C. jejuni strains. This media can be used to design reproducible assays that can help to better understand adaptation, stress resistance and virulence mechanisms of this pathogen. We have shown that with a well curated metabolic model it is possible to design a media to grow this fastidious organism. This has implications for the investigation of new Campylobacter 24 species defined through metagenomics, such as C. infans.